2014
DOI: 10.1016/j.matdes.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical analysis of micromechanical damage in the punching process for High-Strength Low-Alloy steels

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. b s t r a c tSequential sheet metal forming processes can result in the accumulation of work hardening and damage effects in the workpiece material. The mechanical strength of the final component depends on the ''evolution'' of these two characteristics in the different production steps. The punching process, which is usually in the beginning of the production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Mechanical conditions (such as tool clearance and feed velocity) of the shearing process were investigated in [26]. Achouri et al [27] looked into the physical damage mechanisms that occur during the punching operation and established relevant numerical models to predict the fracture location.…”
Section: H Gürün M Göktaş a Güldaş Experimental Examination Of Ementioning
confidence: 99%
“…Mechanical conditions (such as tool clearance and feed velocity) of the shearing process were investigated in [26]. Achouri et al [27] looked into the physical damage mechanisms that occur during the punching operation and established relevant numerical models to predict the fracture location.…”
Section: H Gürün M Göktaş a Güldaş Experimental Examination Of Ementioning
confidence: 99%
“…Mori et al [23] developed a slight clearance punching process using a small round edge to improve the quality of the sheared edge, and they found that the delayed fracture did not happen and the fatigue strength was enhanced due to the large compressive stress around the sheared edge in such punching process. In addition, Achouri et al [24] investigated the physical damage mechanisms in punching operation, and further established an improved numerical formula to predict the fracture location based on the micromechanical approach. Furthermore, Liu and Fu [25,26] proposed a modified ductile criterion for fracture prediction of sheet metal forming, and verified its validity by flexible die forming and hemispherical bulging.…”
Section: Introductionmentioning
confidence: 99%
“…ACCEPTED MANUSCRIPT 3 dealt with the effects that the punching-clearance [8], burr-direction [10,13], cracks, and micro-voids in the edge of a hole [14,16] exert on the stretch-flange formability. However, the effects of the microtexture evolution that develops at the edge of the punched hole on stretch-flange formability have not been properly examined.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…FEA can use spatial distribution, crystallographic orientation and volume fraction of the real microstructure to simulate micromechanical deformation behaviors in the constituent phases during the expansion of a hole [16][17][18][19]. Most FEA has been limited to explaining the deformation and fracture behaviors in the edge of a punched hole, but the microtexture evolution that is induced by the punching of a hole has not been properly investigated [13,16,20,21,23]. An understanding of the microtexture evolution that is induced by the punching of a hole is required in order to perform a more accurate analysis of the HER.…”
Section: Accepted Manuscriptmentioning
confidence: 99%